(untitled) (The Research of Medical Science Review, 2024)
Enzymes are pivotal in biochemical catalysis, driving reactions essential for life and numerous industrial processes. This review explores the fundamental principles of enzyme catalysis, including their structure, mechanisms of action, and factors influencing activity. Advances in enzyme engineering, such as site-directed mutagenesis, directed evolution, and computational approaches, have revolutionized the field, enabling the development of enzymes with enhanced efficiency, specificity, and stability. High-throughput screening and metagenomics have further facilitated the discovery of novel enzymes, while advanced techniques like X-ray crystallography and cryo-EM provide deeper mechanistic insights. The applications of enzyme catalysis are vast, spanning industries such as pharmaceuticals, food processing, biofuels, and environmental sustainability. Enzymes are employed in drug synthesis, chiral compound production, waste management, and green chemistry initiatives, showcasing their versatility and ecological benefits. Despite these advancements, challenges such as stability under extreme conditions, substrate specificity, and production costs remain significant barriers. Looking forward, emerging technologies like synthetic biology, nanotechnology, and artificial intelligence offer promising solutions to overcome these limitations and expand the potential of enzyme applications. This review highlights the transformative impact of enzymes in science and industry, emphasizing their continued importance in advancing sustainable and innovative solutions.